Safe patient monitoring is challenging but still feasible in a neonatal intensive care unit with single family rooms. (11th March 2015) - van Pul, C.; v.d. Mortel, H.P.M.E.; v.d. Bogaart, J.J.L.; Mohns, T.; Andriessen, P.
Abstract Aim Patient monitoring generates a large number of alarms. The aim of this study was to evaluate the rate, type and management of alarms and to determine the risks of a distributed alarm system in a neonatal intensive care unit (NICU) with single family rooms. Methods A risk analysis was performed before implementation. Alarms from patient monitors recorded for a year were identified, classified and counted. The first alarms, which went to the nurse responsible for the patient, were distinguished from the repeat alarms that were generated if the nurse failed to respond within 45 sec. Results The alarm handling protocol was changed as staff felt they needed a greater overview of the NICU alarms to avoid risks. In 1 year, 222 751 critical alarms including 12 309 repeat alarms were generated by patient monitors, equivalent to two alarms per patient per hour. Most of the alarms were oxygen desaturation alarms, followed by bradycardia alarms. About 3% of the desaturation alarms and 0.2% of the bradycardia alarms were repeated. Conclusion Safe patient monitoring was challenging in a NICU with single family rooms, but possible by employing a distributed alarm system. The low number of repeat alarms indicated quick response times.